The Tropical Timber Trade Regime - Gale, F. author. aut Link
XVI, 287 p.
Keywords: Gale explains why international negotiations have not produced a sustainable solution to tropical rainforest degradation. Using an innovative, critical approach to international regimes, the author analyzes the structure and operation of the International Tropical Timber Organization (ITTO). He shows how the timber industry and producing- and consuming-country governments created a blocking alliance that favoured developmentalist interests and ideas. The ITTO bolstered this alliance by permitting environmentalists merely to voice, but not to negotiate, their concerns.